2009
DOI: 10.1080/10837450902891360
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically based pharmacokinetics (PBPK)

Abstract: Allometric scaling is widely used to predict human pharmacokinetic parameters from preclinical species, and many different approaches have been proposed over the years to improve its predictive performance. Nevertheless, prediction errors are commonly observed in the practical application of simple allometry, for example, in cases where the hepatic metabolic clearance is mainly determined by enzyme activities, which do not scale allometrically across species. Therefore, if good correlation was noted for some d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(76 citation statements)
references
References 89 publications
0
76
0
Order By: Relevance
“…PBPK models are used to predict the time-course of a chemical in the blood or specific organs (i.e., the internal dose) affected by the agent (34). These computer-enabled models take into account key anatomical, physiological and biochemical features of laboratory animals and humans, as well as physicochemical properties of the compound of interest.…”
Section: Discussionmentioning
confidence: 99%
“…PBPK models are used to predict the time-course of a chemical in the blood or specific organs (i.e., the internal dose) affected by the agent (34). These computer-enabled models take into account key anatomical, physiological and biochemical features of laboratory animals and humans, as well as physicochemical properties of the compound of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were anesthetized with 50 to 100 mg/kg sodium pentobarbitone 5 to 10 min prior to blood collection. Blood was harvested from groups of mice (n ϭ 5) by cardiac puncture at 10,15,20,30,45,60,75, and 90 min; 2, 2.5, 3,4,5,8,12,18,24,30,36,48, and 56 h; and 3, 4, 5, and 7 days into 1-ml lithium heparin tubes (Vacutainer; Becton Dickinson, Franklin Lakes, NJ) and centrifuged at 3,000 ϫ g for 10 min, and the plasma was separated and stored at Ϫ80°C until analyzed by high-performance liquid chromatography (HPLC) for CQ and DCQ measurement (31). A peripheral blood film was prepared from each mouse prior to CQ dosing and at the time of euthanasia to confirm that the parasitemia data in the pharmacokinetic study mice were consistent with the pharmacodynamic study (data not shown).…”
Section: Maymentioning
confidence: 99%
“…These models allow quantitative assessment of the relation between neuro-PK and TO. As already discussed, PBPK modeling is particularly useful in translating the obtained information from animals to humans by using the available knowledge on species-dependent physiological characteristics such as blood flow and organ volumes [53][54][55].…”
Section: Target Binding Kineticsmentioning
confidence: 99%